2021
DOI: 10.1039/d0ra08230a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of superparamagnetic Fe3O4@noble metal core–shell nanoparticles by thermal decomposition and hydrothermal methods: comparative study and catalytic applications

Abstract: We report on developing a facile synthetic route for reusable nanocatalysts based on a combination of the supermagnetic properties of magnetite with the unique optical and catalytic properties of noble metal hybrid nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…TEM images revealed that the obtained Fe 3 O 4 @MOF(Co) nanoparticles showed a clear core−shell structure with a magnetic core surrounded by a layer of MOF shell with an average thickness of tens of nanometers, indicating that MOF was successfully coated onto the surface of Fe 3 O 4 nanoparticles 422), ( 511), (440), and (622), respectively. 30 As for the XRD pattern of the MOF(Co), all of the well-defined diffraction peaks of the as-synthesized MOF match well with the XRD patterns that are reported in the literature and are consistent with the simulated crystalline structure based on the crystallographic information file from Cambridge Crystallographic Data Centre (CCDC 985792) (Figure 3b). 31 Peaks in the XRD diffraction analysis of Fe 3 O 4 @MOF could be related to either crystalline Fe 3 O 4 or MOF, with no impurity peaks detected, which indicated the successful synthesis of Fe 3 O 4 @ MOF rather than a physical mixture (Figure 3b).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…TEM images revealed that the obtained Fe 3 O 4 @MOF(Co) nanoparticles showed a clear core−shell structure with a magnetic core surrounded by a layer of MOF shell with an average thickness of tens of nanometers, indicating that MOF was successfully coated onto the surface of Fe 3 O 4 nanoparticles 422), ( 511), (440), and (622), respectively. 30 As for the XRD pattern of the MOF(Co), all of the well-defined diffraction peaks of the as-synthesized MOF match well with the XRD patterns that are reported in the literature and are consistent with the simulated crystalline structure based on the crystallographic information file from Cambridge Crystallographic Data Centre (CCDC 985792) (Figure 3b). 31 Peaks in the XRD diffraction analysis of Fe 3 O 4 @MOF could be related to either crystalline Fe 3 O 4 or MOF, with no impurity peaks detected, which indicated the successful synthesis of Fe 3 O 4 @ MOF rather than a physical mixture (Figure 3b).…”
Section: Resultssupporting
confidence: 86%
“…The phase and structure characteristics of Fe 3 O 4 , MOF­(Co), and Fe 3 O 4 @MOF­(Co) were examined by X-ray diffraction (XRD), Fourier transform infrared spectra (FTIR), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). As shown in Figure S4, Fe 3 O 4 nanoparticles yielded the characteristic XRD peaks indexed at 2θ = 30.01, 35.40, 43.19, 53.30, 57.09, 62.82, and 74.36°, which correspond to the reflection plane indices of (220), (311), (400), (422), (511), (440), and (622), respectively . As for the XRD pattern of the MOF­(Co), all of the well-defined diffraction peaks of the as-synthesized MOF match well with the XRD patterns that are reported in the literature and are consistent with the simulated crystalline structure based on the crystallographic information file from Cambridge Crystallographic Data Centre (CCDC 985792) (Figure b) .…”
Section: Resultsmentioning
confidence: 91%
“…No noticeable changes in the XRD pattern have observed after the run of dye adsorption process; however, there is remarkable reduction in the peak intensities and appearance of new peaks. These findings agree with those of 1 , 35 , 44 .
Figure 6 XRD pattern of Fe 3 O 4 -NPs ( a ), chitosan ( b ), MchiBs ( c ) and MchiBs after dye biosorption ( d ).
…”
Section: Characterizationsupporting
confidence: 92%
“…The changes in the peak intensity indicate interaction and entanglement with other components. The peak intensity in the nanocomposite is reduced, indicating the formation of a nano-system with an amorphous structure [ 116 , 117 , 118 ]. The result of placing 5-FU in the nano-system is shown in Figure 2 e. Pure fluorouracil has strong peaks at of 22°, 19°, and 16°, which indicates the crystalline nature of this drug.…”
Section: Resultsmentioning
confidence: 99%